PERILAKU PENGGUNAAN INTERNET BANKING SEBAGAI ALAT TRANSAKSI FINANSIAL: BEHAVIORAL USAGE OF INTERNET BANKING AS FINANCIAL TRANSACTION TOOL - Intan Ika Putri Heryani; Megawati Simanjuntak; Agus Maulana (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
Internet banking is one of the bank services to do financial and non-financial transactions via an internet network. Internet banking provides consumers’ benefits such as fast, safe, convenient, and inexpensive transactions. Moreover, the bank gains business expansion and customer loyalty as their own benefits. Internet banking usage is influenced by perceived usefulness, perceived ease of use, visibility, enjoyment, social influences, attitude toward using, behavioral intention, and actual usage. The study’s purpose was to analyze these variables and formulate managerial implications in developing internet banking for the future. The study approach used the Technology Acceptance Model (TAM), which was tested by Structural Equation Modeling (SEM). The results showed five-factor relationships. First, the perceived ease of use had a significant influence on perceived usefulness. Second, the perceived usefulness was a significant toward the behavioral intention. Third, visibility and enjoyment had significant influence on attitude toward using. Fourth, the attitude toward using had significantly influenced behavioral intention. Five, the behavioral intention had significant toward actual usage. While the variable of visibility and enjoyment indirectly affected the actual usage. Keywords: internet banking, perceived ease of use, perceived usefulness, behavioural intention, visibility Abstrak: Internet banking merupakan salah satu bentuk layanan perbankan kepada nasabah untuk melakukan transaksi perbankan seperti transaksi finansial dan nonfinansial melalui jaringan internet. Internat banking dapat memberikan keuntungan bagi nasabah berupa layanan perbankan yang cepat, aman, nyaman, dan murah, sementara dari segi perusahaan dapat memberikan manfaat seperti perluasan usah dan, kesetiaan pelanggan. Beberapa variabel yang mempengaruhi penggunaan internet banking diantaranya, yaitu perceived usefulness, perceived ease of use, visibility, enjoyment, social influent, attitude toward using, behavioral intention, dan actual usage. Tujuan dari penelitian ini adalah untuk menganalisis variabel tersebut dan merumuskan implikasi manajerial yang dapat diterapkan dalam mengembangkan internet banking untuk perusahaan. Penelitian menggunakan pendekatan Technology Acceptance Model (TAM) dengan uji statistik menggunakan teknik Structural Equation Modelling (SEM). Hasil penelitian menunjukkan perceived ease of use berpengaruh signifikan terhadap perceived usefulness, perceived usefulness berpengaruh signifikan terhadap behavioral intention, visibility dan enjoyment berpengaruh signifikan terhadap attitude toward using, attitude toward using berpengaruh signifikan terhadap behavioral intention dan behavioral intenton berpengaruh signifikan terhadap actual usage. Variabel visibility dan enjoyment secara tidak langsung berpengaruh terhadap actual usage. Kata kunci: internet banking, perspektif kemudahan pengaplikasian, perspektif penggunaan, niat berperilaku, visibilitas